PENERAPAN CAKAP DIGITAL PADA UMKM PENJAHIT MERAPI KELURAHAN TANJUNGPINANG TIMUR - Muqtafin, Muqtafin; Leindarita, Betty; Basyid, Abdul (Jurnal Pengabdian, Pembelajaran dan Pemberdayaan Ekonomi Masyarakat (JP3EM), 2024)
The aim of this service is to educate and encourage MSME players to utilize digital marketing to improve the MSME economy during the Covid 19 pandemic. This service is specifically offered to MSMEs at Penjahit Merapi. To answer the challenges faced by Merapi Tailor MSMEs, our group will carry out a program consisting of: a) developing a digital marketing strategy; b) understand the market, accessibility, types and features; and c) realizing the importance of digital literacy in the market. This program will be implemented through various methods such as outreach, interviews and direct training